PENGARUH EDUKASI NUTRISI KEPADA IBU OBESITAS DENGAN ANAK STUNTING TERHADAP PENURUNAN BEBAN GANDA MALNUTRISI DI KECAMATAN SERANG BARU-KABUPATEN BEKASI - Arifianti Essen, Amanda; Bambang Sutjiatmo, Afifah; Hermanto, Faizal (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
The double burden of malnutrition (obese mothers with stunted children) has become an important focus in the field of public health both in Indonesia and the world. Serang Baru District, Bekasi Regency, is one of the areas in Indonesia that has a significant prevalence of stunting and obesity. This study aims to determine the effectiveness of nutritional education interventions for obese mothers of stunted children on changes in the status of the double burden of malnutrition in the household. The research began with collecting sociodemographic, anthropometric and food intake data for the past 2x24 hours. Respondents who met the inclusion criteria were then given a face-to-face nutrition education intervention every week for 3 months. In the third month, all respondents had their data collected again in the form of anthropometric data and food intake data. The results of the study showed that after the nutritional education intervention was carried out there was a change in the child's HAZ score from -2.87 ± 0.56 to -2.61 ± 0.62, while the mother's BMI was originally 32.52 ± 2.48 to 31.72 ± 2.16 which was significantly different when compared to before the intervention (P<0.05). It can be concluded that nutrition education interventions can reduce the double burden of malnutrition in Serang Baru District, Bekasi Regency.